Dakwah Patterns and Communication of Student Character Program at Al-Fityan Kubu Raya - Muh. Gitosaroso; Harjani Hefni (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
This study aims to determine the pattern of da'wah and communication used by the Al-Fityan Kubu Raya Foundation in forming students' Akhlaq al-Karimah in established character education programs, both in schools and in dormitories. The research was conducted using a descriptive approach obtained through interviews, observation, and documentation. Based on the data obtained, the da'wah pattern carried out by the Al-Fityan Foundation was bi al-lisan (warnings, calls, appeals, and words), bi al-hal (through examples of behavior directly given by educators/mentors), and bi al-arkan (through the rules). Meanwhile, the communication pattern is face-to-face through various learning models, namely: Circular, straight back, and Letter U in the character education mentoring program.